Terra-i, a Bioversity–CIAT-developed environmental monitoring tool supports reduced deforestation globally - Reymondin, Louis; Paz, Paula Andrea; Nguyen, Thuy; Tello, Jhon Jairo; Perez, Jorge Andres; Luong, Phuong (2025)
Terra-i has become crucial in proactive environmental management, offering near real-time deforestation alerts. Institutions gain precise data to drive conservation strategies by leveraging high-resolution sentinel imagery. Its expansion from Latin America to Africa and Asia countries underscores its scalability and adaptability. In countries where deforestation alerts have been implemented, such as Colombia, Ethiopia, and Vietnam, calibrated and validated alerts support law enforcement, while global organizations use their insights for broader policy frameworks. Strengthening local capacities and fostering informed decision-making, Terra-i continues to shape sustainable land-use practices worldwide.